Surface ozone response to satellite-constrained NOx emission adjustments and its implications - Bae, Changhan; Kim, Hyun Cheol; Kim, Byeong Uk; Kim, Soontae (Environmental Pollution, 2020)
Both surface and satellite observations have shown a decrease in NOx emissions in East Asian countries in recent years. In order to reflect the recent NOx emission reduction and to investigate its impact on surface O3 concentrations in Asian megacities, we adjusted two bottom-up regional emission inventories of which base years are 2006 (E2006) and 2010 (E2010), respectively. We applied direct and relative emission adjustments to both E2006 and E2010 to constrain NOx emissions using OMI NO2 vertical column densities. Except for the relative emission adjustment with E2006, modeling results with adjusted emissions exhibit that NOx emissions over East Asian megacities (Beijing, Shanghai, Seoul, and Tokyo) in the bottom-up inventories are generally overestimated. When the direct emission adjustment is applied to E2006, model biases in the Seoul Metropolitan Area (SMA), South Korea are reduced from 24 ppb to 2 ppb for NOx (=NO+NO2) and from −9 ppb to 0 ppb for O3. In addition, NO2 model biases in Beijing and Shanghai in China are reduced from 8 ppb to 18 ppb–0 ppb and 1 ppb, respectively. Daily maximum 8-h average O3 model biases over the same places are decreased by 8 ppb and 14 ppb. Further analyses suggest that the reduction in domestic South Korean NOx emissions plays a significant role in increasing O3 concentrations in SMA. We conclude that the current strong drive to reduce NOx emissions as part of the strategy to lower particulate matter concentrations in South Korea can account for increased O3 concentrations in recent years and suggest that more aggressive NOx emissions will be necessary soon. Recent reductions in NOx emissions over East Asian megacities may have promoted the increase of O3 concentrations. It implies that insightful emission regulations that consider chemical characteristics are required.
Keywords: Chemical characteristic; Chemical regimes; Control policy; NOx emissions; Satellite data; Satellite observations; Seoul metropolitan area; Vertical column densities; Air Pollutants; Beijing; China; Nitrogen Oxides; Ozone; Republic of Korea; Seoul; Tokyo; Vehicle Emissions; Control policy; NOx emissions; Ozone chemical regime; Satellite data